Impact of Gender on Remittances Patterns and Length of Stay in Foreign Employment in Dharan - Khatiwada, Sita Kumari (Dristikon: A Multidisciplinary Journal, 2026)
In countries like Nepal, where remittances account for more than 25% of GDP, gender disparities in remittance flows remain significant. Female migrants, although often earning less, tend to send a higher proportion of their income back, prioritising investments in education and health, and male migration is often focused on immediate poverty reduction. The main objective of this study is to examine the effect of expatriates' gender on the timing of departure and remittance receipt in Dharan. Data were collected through direct personal interviews with 396 individuals using simple random sampling. The collected data were analysed through descriptive statistics using SPSS. The ANOVA test shows the relationship between the dependent and independent variables. In this finding, there is no significant relationship between gender, time spent abroad, and receipt of remittances. Similarly, the planners and policymakers of the Dharan sub-metropolitan city should formulate a suitable policy and invest remittance income in human capital to prevent future brain drain and create a policy to use the country's wealth for sustainable development.